2018
DOI: 10.1016/s2095-3119(17)61777-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomes of early developing tassels under drought stress reveal differential expression of genes related to drought tolerance in maize

Abstract: The development of tassels, the male reproductive organs in maize, is adversely affected by drought during tasseling. To investigate drought tolerance mechanisms at the transcriptome level during early tassel differentiation, RNA-Seq was performed using RNA isolated from early developing tassels sampled from 10 drought-stressed maize inbred lines and their corresponding well-watered treatment (control). The most active pathways were related to metabolic regulation at the RNA level. Expression of genes encoding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 37 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…Particularly in maize, several drought stress response studies have employed the use of RNA-seq technology. The gene expression profiles of maize developing tassels under water deficit conditions were monitored and the results indicated that the up-regulated genes involved in carbohydrate and lipid metabolism were critical in effecting drought tolerance [31]. Moreover, in our previous study, we highlighted the role protein ubiquitination play in coordinating cellular crosstalk between stress and hormone signaling in maize seedlings under drought stress conditions [32].…”
Section: Introductionmentioning
confidence: 93%
“…Particularly in maize, several drought stress response studies have employed the use of RNA-seq technology. The gene expression profiles of maize developing tassels under water deficit conditions were monitored and the results indicated that the up-regulated genes involved in carbohydrate and lipid metabolism were critical in effecting drought tolerance [31]. Moreover, in our previous study, we highlighted the role protein ubiquitination play in coordinating cellular crosstalk between stress and hormone signaling in maize seedlings under drought stress conditions [32].…”
Section: Introductionmentioning
confidence: 93%
“…More remarkably, the 'response to abiotic stimulus' and 'response to stress' related DEGs in cluster 7, including HSPs, DHNs, PRs, AP2-EREBP and WRKY, showed high expression under drought conditions at the VT stage, but low expression at the V12, R2 and R4 stages (S4 Table). A large number of researches have reported these stress responsive genes to play vital roles in maize drought stress response [21,22]. Meanwhile, as for the R2 stage, plant hormone signaling related genes in cluster 4, including brassionosteroid receptors (BRs) and ABA; NAC-transcription; and stress-induced protein, PRs were down-regulated.…”
Section: Specific Expression Patterns Of the Drought-responsive Genesmentioning
confidence: 99%
“…Transcriptome analysis using RNA-sequencing (RNA-seq) has offered us convenience in detecting novel genes in a tissue-or cell-specific manner and enabled us to identify transcriptomic changes under certain biological conditions [19]. RNA-seq has been successfully applied in global gene expression profiling in maize response to drought stress [20][21][22]. Despite all this progress, however, most of these transcriptome researches in maize have focused on a single stage separately, especially the seedling [22], vegetative [20] or reproductive [19] stages.…”
Section: Introductionmentioning
confidence: 99%
“…Plants are subjected to a variety of environmental pressures throughout their life cycles, for example, cold, heat, drought, salt, etc., which have a significant impact on plant activities and the formation of crop yields [1][2][3][4][5]. Recent studies have shown that drought is the major environmental determinant of plant productivity; the drought-induced crop losses nearly equal to those caused by all other natural disasters combined [6][7][8].…”
Section: Introductionmentioning
confidence: 99%